PENGARUH RASIO KEUANGAN, KONDISI PASAR MODAL, DAN PERUBAHAN NILAI TUKAR TERHADAP RETURN SAHAM - Handara, I Made Panji Dwitya Putra Pradnya; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen; Vol 6 No 2 (2017), 2017)
This study aimed to determine the impact of financial ratio (ROE, DER, EPS, and CR), condition of capital market (IHSG), and changes of exchange rates (Rupiah to US Dollar) on stock return of food and beverage companies in Indonesia Stock Exchange. This study was used food and beverage companies that listed on Indonesia Stock Exchange in 2011-2015. Sample chosen by non-probability sampling method with census technique. The analysis technique applied was multiple linear regression. Based on the result of the analysis in 11 companies, the conclusion are: partially ROE, EPS, and CR have significant positive effect on stock return, DER has significant negative effect on stock return, and changes of exchange rates has no significant positive effect on stock return.
Keywords: stock return, financial ratio, condition of capital market, exchange rate